Political functions of impunity in the war on terror: evidence from Afghanistan - Rangelov, Iavor (2019)
The prevalence and persistence of impunity for human rights violations in the war on terror have attracted significant interest from scholars and practitioners. Insufficient attention, however, has been paid to the ways in which impunity might be shaping key objectives and practices of the war on terror and enabling or constraining their pursuit in war zones. Drawing on insights from security cultures theory and analysis of empirical evidence from Afghanistan, this article demonstrates how impunity serves as a mechanism for reproduction and diffusion of the security culture of the war on terror and for cooption and subversion of central components of another security culture: the liberal peace. The argument is elaborated by investigating the functions of impunity in generating the kind of politics that justify an endless war and facilitate the pursuit of its shifting goals and methods. The article suggests that the role of impunity in shaping global security pathways might be more significant than previously understood and highlights the potential of security cultures theory to help explain human rights outcomes in counterterrorism and peace operations